Campos de força para predição da adsorção em faujasitas: metodologia empírica - Gomes, Victor Aias Martins (2015)
The environmental needs and the great economic interest involved. The capture, storage and separation of gases in combustion processes is considered an important step in the development and consolidation of new technology, The separation of acidic gases (CO2 and H2S) is an important step to reduce environmental impacts and meet safety specifications and market. The adsorption on faujasitas presents itself as an economically attractive alternative in industrial processes, but the high number of processes and temperature and pressure conditions where it can be used, makes an experimental study impractical. Another relevant factor are security conditions imposed during the handling of hydrogen sulphide, necessitating greater investment in equipment, maintenance and safety systems. On said the molecular simulation can be used to obtain indispensable properties for the design and deployment of PSAs. The molecular simulation basis is the force field determination. In this work a set of force field parameters, based on classical force fields (UFF), has been proposed for CO2 in sodium faujasitas. The same methodology was used for H2S, N2, O2 and CH4 parameterization. The results obtained at low pressure were compared with experimental studies and other models proposed by literature, obtaining excellent concordance in different temperatures and Si/Al ratios, allowing determining the placement of adsorption sites and the heat. Other balancing cations were tested to predict nitrogen adsorption. The isotherms for the monovalent cations obtained high precision, to the bivalent results represented the standard experimental adsorption isotherms, albeit with less precision. Finally, the adsorption of mixture N2/CO2 was studied presented good agreement with experimental data, demonstrating the efficiency of the method as an alternative for determination of industrial properties of mixtures